Does manufacturers' size affect the prevalence of mycobiota and occurrence of mycotoxins in spices and spice-based products? - Ahmad Zaidi, A. I.; Ghazali, M. A. A.; Nik Muhammad, N. A.; Sazali, N. S.; Mahror, Norlia; Yazid, Siti Nur Ezzati; Selamat, Jinap; Samsudin, Nik Iskandar Putra (Wageningen Academic Publishers, 2020)
The present work aimed to establish the prevalence of mycobiota and occurrence of mycotoxins (aflatoxins and ochratoxin A) in spices and spice-based products, and correlate these to their manufacturers’ sizes. A total of 90 spice, sauce and paste samples were purchased; 3 manufacturer sizes (small, medium, large) × 3 types of samples (spices, sauces, pastes) × 5 brands × 2 replicates. The prevalence of mycobiota was assessed with dichloran rose bengal chloramphenicol (DRBC) and Aspergillus flavus and Aspergillus parasiticus (AFPA) medium, while the occurrence of mycotoxins was quantified with HPLC-FLD. Large-scale manufacturers were found to adopt a greater number of safety and quality certifications. Small-scale manufacturers significantly yielded the highest total fungal loads on DRBC (log 5.084±0.417 cfu/g paste, log 6.253±0.407 cfu/g sauce, log 6.662±0.222 cfu/g spice) and AFPA (log 4.461±0.451 cfu/g paste, log 5.661±0.395 cfu/g sauce, and log 6.269±0.432 cfu/g spice). Correlation analysis (Pearson’s r) revealed that manufacturers’ sizes positively influenced (DRBC r=0.781; AFPA r=0.702) the prevalence of mycobiota. Aflatoxin B1 was present in 6/30 (20%) paste samples, 1/30 sauce samples (3.33%) and 12/30 spice samples (40%). Aflatoxin B2 was only present in 2/30 sauce samples (6.67%). Aflatoxin G1 and G2 were absent from all samples. Ochratoxin A was present in 11/30 (36.67%) paste samples, 5/30 sauce samples (16.67%) and 21/30 spice samples (70%). It was found that, to a certain extent, the size of and certification adopted by manufacturers affected the prevalence of mycobiota and the occurrence of mycotoxins in spices and spice-based products analysed in the present work. Nevertheless, it is henceforth recommended that a surveillance study of this nature be extended and widened in terms of number of samples as well as type of spices, sauces and pastes to obtain a more thorough and significant profile of the products’ food safety and quality level.